Science-Fiction Fans in Socio-Economic Perspective: Factors in the Social Consciousness of Genre. - Berger, Albert I. (Science Fiction Studies)
The article discusses science fiction (SF) in the 1930s, which is considered as the base for science-fiction audience. SF fans are divided into two groups: those interested in film and television SF, and members of the cult following the television series "Star Trek." Till the 1960s, SF has been the traditional domain of men. SF novels were written by males for male readers.